Considering the effect of Pi rebinding on myosin dynamics based on the distinct functions of cardiac and skeletal myosin - Kaya, Motoshi (Frontiers in Physiology, 2025)
In recent years, significant advances have been made in various fields related to the study of myosin, including muscle fiber research, structural studies, and single-molecule measurements. These advances have provided detailed insights into the chemical and mechanical dynamics of myosin. As a result, numerous studies have been conducted on the temporal relationships between phosphate (Pi) release and force generation via myosin structural changes. These structural changes are a critical step in the myosin mechanochemical cycle. Two models have been proposed to explain this process. The first model proposes that force is generated by power stroke after Pi release, while the second model proposes that Pi is released after force generation by the power stroke. Furthermore, a comprehensive model has been proposed to elucidate phenomena predicted by both models. In this article, we explore the structural changes in myosin associated with Pi binding from a different perspective, based on our research, suggesting that the molecular structural dynamics associated with Pi rebinding, as well as its impact on force generation in molecular ensembles, exhibit distinct characteristics between cardiac myosin and skeletal myosin. It is widely acknowledged that an excessive increase in Pi concentration can adversely affect contraction function and contribute to the development of contraction-related diseases in both cardiac and skeletal muscle. In response to such adverse conditions, cardiac and skeletal myosin may employ different mechanisms to counteract the reduction in contractile capacity. Examining these potential mechanisms could facilitate the development of novel therapeutic strategies.